Multi-inflammatory Syndrome in Children Related to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Spain. (25th July 2020) - Moraleda, Cinta; Serna-Pascual, Miquel; Soriano-Arandes, Antoni; Simó, Silvia; Epalza, Cristina; Santos, Mar; Grasa, Carlos; Rodríguez, Maria; Soto, Beatriz; Gallego, Nerea; Ruiz, Yolanda; Urretavizcaya-Martínez, María; et al.
Abstract: Some clusters of children with a multisystem inflammatory syndrome (MIS-C) associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been reported. We describe the epidemiological and clinical features of children with MIS-C in Spain. MIS-C is a potentially severe condition that presents in children with recent SARS-CoV-2 infection.